Penguatan Kesadaran Lingkungan Masyarakat melalui Penyuluhan Pengolahan Sampah Organik menjadi Kompos di Desa Perian, Kabupaten Lombok Timur - Humairo Saidah; I Wayan Yasa; I Dewa Gede Jaya Negara; Hasyim; Rohani; I Dewa Made Alit Karyawan; Salehudin; Muh Bagus Budianto; Tri Rachmanto; Nur Chayati; Yesung Allo Padang (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Perian Village, located in Montong Gading District, East Lombok Regency, is a tourism village with considerable natural potential that should be supported through sustainable environmental management. One of the challenges faced by the community is household waste management. Household waste is generally collected and transported for disposal, creating a burden on the village government, which has limited financial resources and waste management facilities. Meanwhile, a large proportion of the waste generated consists of organic materials that can be utilized as a valuable resource through composting. This community service program aimed to enhance community knowledge and awareness of organic waste management and encourage the conversion of organic waste into compost. The program was conducted on January 23, 2026, at the Perian Village Sports Hall using an educational outreach approach consisting of lectures, discussions, and question-and-answer sessions. The topics covered included waste-related issues, the impacts of improperly managed waste on public health and the environment, the benefits of organic waste management, and simple household-scale composting techniques. Program evaluation was carried out through observation of participant engagement and responses during the activity. The results showed a highly positive response from the participants. Community enthusiasm was reflected in the high attendance rate and active participation in discussions. Participants demonstrated an improved understanding of the importance of organic waste management and the benefits of composting. They also expressed their commitment to sorting and processing household organic waste into compost. The program successfully increased public awareness of compost-based organic waste management. To ensure long-term sustainability, follow-up assistance and hands-on composting activities are recommended at the community level.